Adaptive Delta Modulation Simulation and Analysis Using MatLab - Djadjat Sudaradjat; Andi Rosano (LPPM Universitas Bina Sarana Informatika, 2023)
The system for converting analog signals to digital signals has become a necessity, considering that the tools currently used are digital computers. One of the analog-to-digital conversion systems is the delta modulation system. In delta modulation, only one bit is used to encode each change in the input signal, where a rising signal is encoded into a one bit and a falling signal is encoded into a zero bit. This can save the bit rate which, when transmitted over the transmission channel, can save the transmission bandwidth, and when stored in computer storage media, can save storage space. However, if the slope of the signal rises and falls sharply, the delta modulation system cannot follow these signal changes, which is called slope overload. To overcome this problem, an adaptive delta modulation system was developed that has variable or adaptive pulse height for both one and zero bits. In this paper, a comparison between the delta modulation system and the adaptive delta modulation system using MatLab application will be simulated and analyzed. From the simulation results, it can be seen that the adaptive delta modulation system is able to overcome slope overload compared to the delta modulation system.